Modulation of Polymorphonuclear Cell Interleukin-8 Secretion by Human Monoclonal Antibodies to Type 8 Pneumococcal Capsular Polysaccharide - Burns, Tamika (American Society for Microbiology, 2003)
Pneumococcal capsular polysaccharide (PS) vaccines induce type-specific immunoglobulin M (IgM), IgG, and IgA. Type-specific IgG to the PS is sufficient to confer protection against the homologous serotype of the pneumococcus, but the efficacies of type-specific IgM and IgA are less well understood. We examined the in vitro activities and efficacies in mice of two human monoclonal antibodies (MAbs) to type 8 PS, NAD (IgA) and D11 (IgM). MAb-mediated opsonophagocytic killing was evaluated after coculture of type 8 pneumococci with human polymorphonuclear cells (PMNs), type-specific or control MAbs, and human complement sources. The effects of the MAbs on PMN interleukin-8 (IL-8) and IL-6 secretion were determined in supernatants from cocultures containing pneumococci and PMNs by enzyme-linked immunosorbent assay. MAb efficacy was determined in an intratracheal model of type 8 infection in mice with classical complement pathway deficiency. Both MAbs were protective in 100% of infected mice. Neither MAb promoted a significant amount of killing of type 8 pneumococci compared to its isotype control MAb. Both type-specific MAbs mediated complement-dependent modulation of PMN IL-8 secretion, with increased secretion at effector/target (E:T) ratios of 500:1 and 50:1 and reduced secretion at 1:5. Trypan blue staining revealed that PMNs cocultured with D11 were less viable at an E:T ratio of 1:5 than PMNs cocultured with the control MAb. PMN IL-6 secretion was increased by both type-specific and control MAbs. These results suggest that certain type-specific IgM and IgAs might contribute to host defense by modulation of the inflammatory response to pneumococci.